The use of the internet by the elderly in the UK and its influence on their well-being - Ortega-Gaspar, María Marta; Gamero-Burón, Carlos (My University, 2013)
The main objetive of the present study is to describe the use of the Internet by elderly in the United Kingdom in order to determine if this use influences their perception of well-being. The structure of the present research is divided into three sections: The first one focuses on a descriptive analysis of the elderly use of Internet in the UK. The second one focuses on an explanatory analysis (logit models) to determine the factors that predispose the UK elderly to use the Internet. The third section offers an explanatory analysis to determine if there are any differences between users and no-users of Internet in the perceptions of the well being . The principal database is UK World Internet Survey (2007 and 2009). We come to the conclusion that the elderly who show the highest propensity to use the Internet are the single, those with university studies, that speak a second language, not disable, with political interest, not religious and living in country village. The results show that the elderly non user of the Internet in the Uk feel more often lack of companionship, left out and isolated than the user ones.
Presentación realizada en el congreso Internacional organizado por la British Society of Gerontology (Septiembre 2013)
Keywords: Internet - Aspectos psicológicos; Internet; Bienestar social; Elderly; Internet; Well-being